Learning, from, with and in India: a study tour of the agroecology initiative - International Water Management Institute (International Water Management Institute, 2023)
Over the last two years of implementing the CGIAR initiative on agroecology, the team has experienced how the application of its principles varies from one context and country to the other. It is therefore important to witness firsthand these very different pathways to achieve agroecological transformations that all aim at enhancing food system resilience, equity and sustainability. The best-known Indian pathway is Natural Farming and the Initiative decided to go on a tour to see and understand the phenomena.